AN ENHANCEMENT OF TC, FROM 45-K TO 70-K, VIA CD SUBSTITUTION IN (PB,CU)SR2(CA,Y)CU2O7-DELTA - Liu, R; Groult, D; Maignan, A; Hu, S; Jefferson, D; Raveau, B; Michel, C; Hervieu, M; Edwards, P (1992)
An enhancement in the superconducting transition temperature, Tc, from 45 K to 70 K, has been discovered during the course of our investigation of Cd-doping of the Pb-based 1212 superconductors. Specifically, we have attempted to synthesize a material with nominal composition (Pb0.5Cd0.5)Sr2 (Ca0.5Y0.5) Cu2O7-δ, derived from the lead cuprate superconductor (Pb0.7Cu0.3) Sr2(Ca0.5Y0.5) Cu2O7-δ. From X-ray and electron diffraction, coupled with energy-dispersive X-ray emission spectrometry, we can identify the phase responsible for the 70 K superconductivity to be (Pb0.67(2)Cd0.33(5))Sr2.1(1)(Cd0.20(3) Ca0.33(3)Y0.48(4))Cu2O7-δ. Thus, we propose substitution of Cd both for Cu, in the rock salt-type (Pb, Cu)O layers, and Ca, in the Ca0.5Y0.5 lattice sites. No superlattice spots or streaks were observed in electron diffraction experiments along the a*, b* and c* directions in the Cd-substituted material.